1989
DOI: 10.1128/jvi.63.2.952-954.1989
|View full text |Cite
|
Sign up to set email alerts
|

Mutations located on both F1 and F2 subunits of the Newcastle disease virus fusion protein confer resistance to neutralization with monoclonal antibodies

Abstract: The fusion gene sequence of six Newcastle disease virus escape mutants revealed that residues important for the integrity of antigenic site 1 and antigenic site 2 were located, respectively, on the F2 subunit and within the cysteine-rich domain of the F1 subunit. We further report the antibody-binding capacity of these mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…This is in agreement with the marginal effect that antibodies binding to site I (located in the middle of the cysteine cluster) have in virus neutralization. Antigenic sites equivalent to those of HRSV F protein have been described in Sendai virus (32), NDV (28,40), and parainfluenza virus type…”
Section: Figmentioning
confidence: 99%
“…This is in agreement with the marginal effect that antibodies binding to site I (located in the middle of the cysteine cluster) have in virus neutralization. Antigenic sites equivalent to those of HRSV F protein have been described in Sendai virus (32), NDV (28,40), and parainfluenza virus type…”
Section: Figmentioning
confidence: 99%
“…Thus, it seems possible that Sendai virus F2 has a noncovalent but tight association with the F1 molecule in addition to the covalent association via the intermolecular disulfide bridge. Interestingly, in this context, studies on neutralization escape mutants of Newcastle disease virus have suggested a topological interrelationship between F1 (heptad repeat A domain or cysteine-rich region) and F2 (10,19). Undoubtedly, further investigation is needed to elucidate the possible role of F2 in the fusogenic activity.…”
mentioning
confidence: 99%
“…VOL. 66, 1992 on July 6, 2020 by guest http://jvi.asm.org/ Downloaded from F protein mutants have been isolated from other strains of NDV by their ability to escape neutralization with F-specific monoclonal antibodies (33,48,53). Interestingly, a major group of antibody escape mutants (amino acids 157 to 171) lies within the AAH described here and overlaps the amino acid 153-159 region containing the DI and D2/D3 mutations and the largest group of revertants.…”
Section: Discussionmentioning
confidence: 99%